2012
DOI: 10.1371/journal.pone.0038710
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Hydroxyapatite Bone Substitutes to Enhance Tissue Regeneration: Evaluation In Vitro Using Osteoblast-Like Cells and In Vivo in a Bone Defect

Abstract: In case of degenerative disease or lesion, bone tissue replacement and regeneration is an important clinical goal. In particular, nowadays, critical size defects rely on the engineering of scaffolds that are 3D structural supports, allowing cellular infiltration and subsequent integration with the native tissue. Several ceramic hydroxyapatite (HA) scaffolds with high porosity and good osteointegration have been developed in the past few decades but they have not solved completely the problems related to bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 32 publications
2
83
1
4
Order By: Relevance
“…However, such concerns have been dissipated by a number of in vivo tests demonstrating that magnetic nanofibrous scaffolds of PCL implanted subcutaneously [93] and magnetic hydroxyapatite/collagen scaffolds implanted in rabbit distal femoral epiphysis and tibial mid-diaphysis did not appear to cause inflammation [94]. Furthermore, magnetic hydroxyapatite, prepared with different ratios of magnetic particles, when implanted in rabbit bone critical size defects produced in the condyle region, had similar biocompatibility to hydroxyapatite alone [95]. Indeed, it has been observed that granting magnetic properties to biomaterials can lead to a significant increase in cell proliferation [95,96].…”
Section: Magnetic Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such concerns have been dissipated by a number of in vivo tests demonstrating that magnetic nanofibrous scaffolds of PCL implanted subcutaneously [93] and magnetic hydroxyapatite/collagen scaffolds implanted in rabbit distal femoral epiphysis and tibial mid-diaphysis did not appear to cause inflammation [94]. Furthermore, magnetic hydroxyapatite, prepared with different ratios of magnetic particles, when implanted in rabbit bone critical size defects produced in the condyle region, had similar biocompatibility to hydroxyapatite alone [95]. Indeed, it has been observed that granting magnetic properties to biomaterials can lead to a significant increase in cell proliferation [95,96].…”
Section: Magnetic Biomaterialsmentioning
confidence: 99%
“…Furthermore, magnetic hydroxyapatite, prepared with different ratios of magnetic particles, when implanted in rabbit bone critical size defects produced in the condyle region, had similar biocompatibility to hydroxyapatite alone [95]. Indeed, it has been observed that granting magnetic properties to biomaterials can lead to a significant increase in cell proliferation [95,96]. The mechanisms underlying this stimulation still need to be elucidated.…”
Section: Magnetic Biomaterialsmentioning
confidence: 99%
“…Some physical stimulation, such as electrical, mechanical, and magnetic stimulation, play key roles in the development and restoration of many tissues, for instance bone tissues, and those stimulations act effectively on bone formation [1][2][3] . Additionally, Static Magnetic Field (SMF) has a wide range of biological effects as a physical factor 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Static Magnetic Field (SMF) has a wide range of biological effects as a physical factor 3) . Studies have demonstrated that SMF could promote bone repairing and formation 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables the long--term drug delivery process and supports tissue regeneration to be controlled adequately to requirement, even for a long period of time after implantation. Additionally, * corresponding author; e-mail: swietek@agh.edu.pl magnetic implants, due to presence of particles possessing magnetic properties, also enhance and accelerate cell proliferation and bone tissue formation under an applied static magnetic eld [16,17].…”
Section: Introductionmentioning
confidence: 99%